Analisis Strategi Pemasaran E-Commerce Moka Gojek Pada Masa Pandemi Covid-19 - Sandi Kameswara; Harya Damar Widiputra (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to: How is the ongoing evaluation carried out on PT Moka Gojek's E-Commerce marketing strategy and how is PT Moka Gojek's E-Commerce marketing strategy planned for business continuity in the future, the research method uses qualitative descriptive methods using the positivism research paradigm, analytical methods The data used by researchers is successive approximation (measurement of success), the results of the research found that the Covid-19 pandemic situation has encouraged Moka Gojek to determine a combination of strategies in the pre-pandemic period with new strategies during the pandemic through several adaptive adjustments to the challenging situations and opportunities that arise. faced. This implementation has been effective and more efficient by successfully increasing the growth of the number of Moka Gojek merchants by 150%. Moka Gojek's marketing strategy during the pandemic has changed, namely by focusing more on interactive and online marketing. Another change that occurred was that Moka Gojek then focused its marketing activities on merchants from the retail and service sectors. This change in focus on marketing strategy aims to maintain the continuity of the Moka Gojek business amidst the decline in the quality of FnB merchants who have been worst affected by the Covid-19 pandemic. Keywords: e-commerce, Covid-19, successive approximation